The Effect Of Olive Oil Application On The Fading Of Stretch Marks In Postpartum Mothers - Handayani, Siska Tri; Rosmiyati, Rosmiyati; Octaviani Iqmy, Ledy (JKM (Jurnal Kebidanan Malahayati), 2024)
Background Olive oil, containing fatty acids, hydrocarbons, carotenes, tocopherols, fatty alcohols, waxes, pigments or chlorophyll, and carotenoids, is known for its beneficial properties in addressing stretch marks. Objective: To determine the influence of olive oil application on the fading of stretch marks in postpartum mothers. Methodology: This was a quantitative study utilizing a true experimental design with a pretest-posttest approach using a control group. The population consisted of 50 postpartum mothers in January 2023. A sample of 30 was divided into two groups. Purposive sampling with the Mann-Whitney U test was employed. The study was conducted from January to July 2023.Result The average stretch mark severity among postpartum mothers before olive oil application in the working area of Seputih Banyak Primary Health Care, Central Lampung Regency, in 2023 was a mean of 5.07, categorized as severe. After olive oil application, the mean decreased to 1.60, indicating a change and reduction in stretch marks, categorized as mild. The statistical test results showed a p-value of 0.000 (<0.05), signifying an influence of olive oil application on the fading of stretch marks in postpartum mothers. The research findings also revealed that age during pregnancy, body mass index during pregnancy, and parity or the number of births influence the occurrence of stretch marks.Conclusion There is a significant effect of olive oil application on the fading of stretch marks in postpartum mothers within the working area of Seputih Banyak Primary Health Care, Central Lampung Regency in 2023.Suggestion : Enhancing pregnant mothers' knowledge regarding stretch marks and the utilization of olive oil in their management. Keywords: Olive Oil, Stretch Marks, Postpartum Mothers ABSTRAKPENGARUH PEMBERIAN MINYAK ZAITUN (Olive Oil) TERHADAP PEMUDARAN STRETCH MARK PADA IBU NIFAS  Latar Belakang Minyak zaitun dengan kandungan asam lemak, hidrokarbon dan bikarotin, tokoferol, fatty alkohol, waxes, pigmen atau klorofil dan karotenoid, sterol yang sangat baik untuk mengatasi stretch mark.Tujuan Penelitian: Diketahui pengaruh pemberian minyak zaitun (Olive Oil) terhadap pemudaran stretch mark pada ibu nifas.Metode Penelitian: Jenis penelitian kuantitatif dengan rancangan true experimental melalui pendekatan pretest-posttest with control grup design. Populasi 50 ibu nifas pada bulan Januari 2023. Sampel sebanyak 30 dibagi 2 kelompok. Teknik sampling menggunakan purposive menggunakan uji mann whiteny u test. Penelitian dilaksanakan Januari-Juli 2023.Hasil Rata-rata stretch mark pada ibu nifas sebelum diberi minyak zaitun di Wilayah Kerja Puskesmas Seputih Banyak Kabupaten Lampung Tengah Tahun 2023 dengan mean 5,07 dengan kategori parah, Sesudah diberi minyak zaitun mean 1,60 mengalami perubahan dan penurunan stretch mark dengan kategori ringan. Hasil uji statistic menunjukkan p-value 0,000 (<0,05) artinya terdapat pengaruh pemberian minyak zaitun (Olive Oil) terhadap pemudaran stretch mark pada ibu nifas. Hasil penelitian menunjukkan bahwa usia saat hamil, indeks massa tubuh saat hamil dan paritas atau jumlah kelahiran mempengaruhi terjadinya stretch mark.Kesimpulan Terdapat pengaruh pemberian minyak zaitun (Olive Oil) terhadap pemudaran stretch mark pada ibu nifas di Wilayah Kerja Puskesmas Seputih Banyak Kabupaten Lampung Tengah Tahun 2023.Saran: Peningkatan pengetahuan ibu hamil terkait stretch mark dan pengunaan olive oil dalam penanganannya. Kata Kunci : Minyak Zaitun (Olive Oil), Stretch Mark, Ibu Nifas